2014
DOI: 10.1161/circoutcomes.114.000804
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quality Measurement for Anticoagulation

Abstract: TTR and INR variabilities measure different characteristics of anticoagulation control.12 TTR reflects the achievement of appropriate intensity, and not necessarily the stability, of the anticoagulation regimen. Conversely, INR variability measures stability, but not intensity, of anticoagulation. One approach to strengthen our prediction about warfarin adverse events would be to combine these measures. Whether the use of both measures jointly will improve risk stratification for ultimate outcomes of interest,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…10 In that study, as in ours, the 2 measures together provided additional, complementary information, as evidenced by better prediction than either one alone. 10 Still another study by Lind et al 17 found that INR variability was a much stronger predictor of outcomes than TTR. In that study, the predictive ability of TTR was so slight that it did not meaningfully add to that of INR variability when combined in one model.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…10 In that study, as in ours, the 2 measures together provided additional, complementary information, as evidenced by better prediction than either one alone. 10 Still another study by Lind et al 17 found that INR variability was a much stronger predictor of outcomes than TTR. In that study, the predictive ability of TTR was so slight that it did not meaningfully add to that of INR variability when combined in one model.…”
Section: Discussionsupporting
confidence: 63%
“…4 Warfarin control is best understood as an intermediate outcome of care, in that control has been correlated with definitive outcomes, such as hemorrhage and stroke. [5][6][7][8][9][10][11] Intermediate outcomes of care are useful for quality assurance and research efforts because they can be assessed with smaller samples and briefer follow-up than are often needed to confidently assess rates of definitive outcomes. 12,13 Using the most predictive intermediate outcome will ensure that efforts to improve performance on intermediate outcomes can achieve the maximum possible benefit for patients.…”
mentioning
confidence: 99%
See 3 more Smart Citations